Closed-Loop Rehabilitation of Age-Related Cognitive Disorders - Mishra, Jyoti; Gazzaley, Adam (Seminars in Neurology, 2014)
Cognitive deficits are common in older adults, as a result of both the natural aging process and neurodegenerative disease. Although medical advancements have successfully prolonged the human lifespan, the challenge of remediating cognitive aging remains. The authors discuss the current state of cognitive therapeutic interventions and then present the need for development and validation of more powerful neurocognitive therapeutics. They propose that the next generation of interventions be implemented as closed-loop systems that target specific neural processing deficits, incorporate quantitative feedback to the individual and clinician, and are personalized to the individual's neurocognitive capacities using real-time performance-adaptive algorithms. This approach should be multimodal and seamlessly integrate other treatment approaches, including neurofeedback and transcranial electrical stimulation. This novel approach will involve the generation of software that engages the individual in an immersive and enjoyable game-based interface, integrated with advanced biosensing hardware, to maximally harness plasticity and assure adherence. Introducing such next-generation closed-loop neurocognitive therapeutics into the mainstream of our mental health care system will require the combined efforts of clinicians, neuroscientists, bioengineers, software game developers, and industry and policy makers working together to meet the challenges and opportunities of translational neuroscience in the 21st century.
Keywords: closed loop; neurotherapeutics; cognitive training; neuroplasticity; personalized medicine